Zika Virus–Associated Neurological Disease in the Adult: Guillain–Barré Syndrome, Encephalitis, and Myelitis - Muñoz, Laura S.; Barreras, Paula; Pardo, Carlos A. (Seminars in Reproductive Medicine, 2016)
Zika virus (ZIKV) has caused a major infection outbreak in the Americas since 2015. In parallel with the ZIKV epidemic, an increase in cases of neurological disorders which include Guillain–Barré syndrome (GBS), encephalitis, and myelitis have been linked to the infection. We reviewed the evidence suggesting a relationship between ZIKV and neurological disorders in adults. A search of the literature supporting such link included databases such as PubMed and the World Health Organization (WHO) surveillance system. Through June 1, 2016, 761 publications were available on PubMed using the search word “Zika.” Among those publications as well as surveillance reports released by the WHO and other health organizations, 20 articles linked ZIKV with neurological complications other than microcephaly. They corresponded to population and surveillance studies (n = 7), case reports (n = 9), case series (n = 3), and case–control studies (n = 1). Articles were also included if they provided information related to possible mechanisms of ZIKV neuropathogenesis. Evidence based on epidemiological and virological information supports the hypothesis that ZIKV infection is associated with GBS. Although cases of encephalopathy and myelitis have also been linked to ZIKV infection, the evidence is scarce and there is a need for virological, epidemiological, and controlled studies to better characterize such relationship.
Keywords: ZIKV; GBS; encephalitis; myelitis; adult